Effect of Prenatal Ketamine Exposure on GFAP Marker Expression in Mice Prefrontal Cortex Mice Prefrontal Cortex - Mghamis, Munqith Mazin (International Journal of Psychosocial Rehabilitation, 2020)
Ketamine, N-Methyl-D-Aspartate receptor antagonist agent, is widely used clinically for anesthesia, particularly in the developing countries. About 2% of pregnant women in the United States required surgeries because of the problems related to the pregnancy itself or due to other medical conditions, and ketamine regarded the first choice of anesthesia. This percentage is increasing, relatively because of laparoscopic procedures and fetal surgery.